Penerapan Assessment Of, For Dan As Learning Dalam Perkuliahan Di Perguruan Tinggi Keagamaan Islam Indonesia - Prihantoro, Agung; Santoso, Fattah Setiawan; Haroen, Hilman (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2024)
The research aims to describe (1) how assessment of learning (AoL), assessment for learning (AfL) and assessment as learning (AaL) are applied by lecturers in Islamic universities in Indonesia, (2) what steps of the AaL the lecturers take, (3) how the lecturers give feedback of the AaL to students in the sociocultural-regious context of Indonesia Islamic universities, and (4) what problems and solutions of applying the AaL. The research methodology is an explanatory sequential mixed-methods. The population is lecturers of Islamic universities in Indonesia and the sample is 108 lecturers by cluster random sampling. The lecturers applying the AoL, AfL and AaL unitedly and separately in high level are 10 (9,26%)—19 (17,59%) people, and those specifically applying the AaL are 10 (9,26%) people. Steps of the AaL taken by the lecturers are (1) writing and distributing teaching plans to students, (2) motivating students to do self-regulated learning, (3) asking students to assess student’s own learning outcome, (4) asking students to assess their colleagues’ learning outcome and (5) giving feedback to students. The lecturers give feedback to students in Indonesia Islamic universities. Problems of applying the AaL deal with the lectuers’ low understanding of the AaL and students’ low level of self-regulated learning.